1997
DOI: 10.1093/ajcn/66.5.1232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition in nonsurgical hospitalized patients and its association with disease complications

Abstract: The prevalence of malnutrition and its predictive value for the incidence of complications were determined in 155 patients hospitalized for internal or gastrointestinal diseases. At admission, 45% of the patients were malnourished according to the Subjective Global Assessment (physical examination plus questionnaire), 57% according to the Nutritional Risk Index [(1.5 X albumin) + (41.7 X present/usual weight)], and 62% according to the Maastricht Index [(20.68 -(0.24 X albumin) -(19.21 X transthyretin (prealbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
183
2
35

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(229 citation statements)
references
References 19 publications
9
183
2
35
Order By: Relevance
“…There was a significant difference in the median length of stay of patients who were well-nourished compared to patients who were moderately or severely malnourished (P ¼ 0.024), with 9% of the variance in length of stay being attributable to nutritional status. This is consistent with the findings of Naber et al (1997) and Reilly et al (1988), who found that malnourished hospital patients had a longer length of stay than wellnourished patients. Although there was a trend towards increased mortality within 30 days of discharge for each of the SGA classifications, this was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…There was a significant difference in the median length of stay of patients who were well-nourished compared to patients who were moderately or severely malnourished (P ¼ 0.024), with 9% of the variance in length of stay being attributable to nutritional status. This is consistent with the findings of Naber et al (1997) and Reilly et al (1988), who found that malnourished hospital patients had a longer length of stay than wellnourished patients. Although there was a trend towards increased mortality within 30 days of discharge for each of the SGA classifications, this was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Undernutrition is considered to be a multifactorial disorder caused by metabolic effects of underlying disease, reduced nutritional intake, and additional factors that might increase the general risk of developing nutritional deficits such as age, therapeutic interventions, educational level, and/or low socioeconomic status of the patient (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition continues to be recognized as a signi®cant component of acute medical illness in 45 ± 62% of hospitalized patients (Naber et al, 1997), ®gures that are unchanged from surveys performed over two decades ago (Weinsier et al, 1979). While convincing controlled studies are often lacking, nutrition support has become a standard of care in the inpatient treatment of the postoperative surgical patient, critically ill patients such as those with severe burns or other trauma, and in diseases that compromise digestion such as severe in¯ammatory bowel disease and the short bowel syndrome .…”
Section: Why Nutrition Education Is Critical To the Practicing Physicianmentioning
confidence: 99%